2013
DOI: 10.1093/jac/dkt023
|View full text |Cite
|
Sign up to set email alerts
|

Trends in antibiotic resistance over time among pathogens from Canadian hospitals: results of the CANWARD study 2007-11

Abstract: Although some of these trends, such as the dramatic increase in fluoroquinolone and cephalosporin resistance in E. coli, can be attributed to the emergence and global spread of resistant clones (e.g. ST131 E. coli), others remain unexplained. However, recognizing these trends remains important to guide changes in empirical antimicrobial therapy and drug development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 32 publications
1
26
0
Order By: Relevance
“…In Canada and Australia, the prevalence of ESBL phenotypes in E coli has roughly doubled from around only 3% five years ago. [33][34][35] Ciprofloxacin resistance in clinical isolates of E coli increased from 5.4% in 2010 to 6.9% in 2012 in Australia, and from 21% to 27% between 2007 and 2011 in Canada, where fluoroquinolone usage has been somewhat higher than in Australia. 33 Fig 1 | Timeline of bacterial evolution.…”
Section: Incidence and Prevalencementioning
confidence: 99%
See 1 more Smart Citation
“…In Canada and Australia, the prevalence of ESBL phenotypes in E coli has roughly doubled from around only 3% five years ago. [33][34][35] Ciprofloxacin resistance in clinical isolates of E coli increased from 5.4% in 2010 to 6.9% in 2012 in Australia, and from 21% to 27% between 2007 and 2011 in Canada, where fluoroquinolone usage has been somewhat higher than in Australia. 33 Fig 1 | Timeline of bacterial evolution.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…[33][34][35] Ciprofloxacin resistance in clinical isolates of E coli increased from 5.4% in 2010 to 6.9% in 2012 in Australia, and from 21% to 27% between 2007 and 2011 in Canada, where fluoroquinolone usage has been somewhat higher than in Australia. 33 Fig 1 | Timeline of bacterial evolution. The introduction of each antibiotic has been quickly followed by recognition of an adaptation (including a phenotype or mechanism, as marked on resistance timeline) to resist it.…”
Section: Incidence and Prevalencementioning
confidence: 99%
“…Although a North America study it should be noted that the majority of North American sites in SMART are located in the US. The CAN-WARD study of Canadian hospitals reported a statistically significant (p < 0.001) decrease in fluoroquinolone (ciprofloxacin) resistance among P. aeruginosa between 2007 and 2011, from 34.0 to 21.8% [17]. However, the isolates in the Lagac eWiens et al study were not solely from IAIs [17].…”
Section: Drug Name (Generic)mentioning
confidence: 88%
“…The CAN-WARD study of Canadian hospitals reported a statistically significant (p < 0.001) decrease in fluoroquinolone (ciprofloxacin) resistance among P. aeruginosa between 2007 and 2011, from 34.0 to 21.8% [17]. However, the isolates in the Lagac eWiens et al study were not solely from IAIs [17]. In their surveillance study of isolates collected from IAIs from US medical centers in 2012, Flamm et al reported that 10.4% of E. coli and 16.3% of Klebsiella spp.…”
Section: Drug Name (Generic)mentioning
confidence: 99%
“…The emergence of bacterial infections resilient to the current arsenal of antibiotics is increasing (Lagace-Wiens et al, 2013;Spellberg et al, 2008;Zhanel et al, 2013), and the challenge in managing this crisis is that the emergence of antimicrobial multiresistant bacteria is a natural process that relies on both the evolutionary changes and the biological components of the microorganisms. These natural processes, which include gene acquisition, transfer and gene expression, provide the organisms with the ability to adapt and evolve within their environments.…”
Section: The Problem Of Antibiotic Resistancementioning
confidence: 99%